Evaluation of electrical properties of paddy husk and husk ash composites for the possibility of high-end alternative usage - Kumar, Anil; Prasad, Kamlesh (Journal of Postharvest Technology, 2020)
Effort is made to introduce a bio-degradable dielectric material using paddy husk and husk ash. Oryza sativa cultivar PUSA 1121 husk (OSH)  and ash (OSA) as a highly compressed mixture in specific ratio depicts enough effect of electric field. Relative permittivity of compressed  OSH-10, OSH-20, OSH-30 are OSH-40 having 10, 20, 30 and 40% husk ash, respectively are found efficient to act as dielectric materials.  Permittivity at different frequencies show relaxing of polarization among dipoles. Variation in permittivity with addition of ash in controlled ratio  is modifying the sample enough to be a suitable material. Resistivity, AC conductivity and dielectric loss of OSH-40 is observed more suitable  for the application of this bio inspired selected material as capacitor. The relation between applied electric field and polarization effect shown  by the dipoles shows the relaxer behavior of the samples, making it suitable for bio- degradable memory devices at ambient temperature. The  findings may be useful for the possible application of paddy husk in high-end utilization.
Keywords: Dielectric permittivity; dielectric loss factor; frequency; addy husk,; ash